2020
DOI: 10.3390/ani10061083
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Parameters of Birth Weight and Weaning Weight and Their Relationship with Gestation Length and Age at First Calving in Hanwoo (Bos taurus coreanae)

Abstract: Hanwoo is one of the most economically important animal species in Korea due to its significant contribution to nutrition. However, the current selection index only focuses to improve carcass traits of Hanwoo. Thus, this study aimed to estimate the genetic parameters of birth weight (BW) and weaning weight (WW) and their genetic and phenotypic relationship to the age at first calving (AFC) and gestation length (GL) of Hanwoo. The genetic parameters for birth weight (BW) and weaning weight (WW) were estimated u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
2
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 32 publications
1
10
2
4
Order By: Relevance
“…The heritability estimate of birth weight in this study was lower than that of the result reported by Fathoni et al [13] for OG cattle in Kebumen Regency, namely 0.76 ± 0.12 and the results of research by Kaswati et al [14] in Bali cattle, namely 0.85 ± 0.44, the result reported by Karnaen [15] in Madura cattle, namely 0.33 ± 0.24, the result reported by Suhada et al [16] in Simental cattle, namely 0.11 ± 0.09 , the result reported by Estrada-León et al [17], namely 0.41 ± 0.09, and the research results of Putra et al ( 2014) [18] in Aceh cattle, namely 0.15 ± 0.13. The heritability value of birth weight of PO cattle as a result of this study is in agreement with the results of Lopez et al [19] research on Hanwoo cattle, which was 0.22 ± 0.02.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The heritability estimate of birth weight in this study was lower than that of the result reported by Fathoni et al [13] for OG cattle in Kebumen Regency, namely 0.76 ± 0.12 and the results of research by Kaswati et al [14] in Bali cattle, namely 0.85 ± 0.44, the result reported by Karnaen [15] in Madura cattle, namely 0.33 ± 0.24, the result reported by Suhada et al [16] in Simental cattle, namely 0.11 ± 0.09 , the result reported by Estrada-León et al [17], namely 0.41 ± 0.09, and the research results of Putra et al ( 2014) [18] in Aceh cattle, namely 0.15 ± 0.13. The heritability value of birth weight of PO cattle as a result of this study is in agreement with the results of Lopez et al [19] research on Hanwoo cattle, which was 0.22 ± 0.02.…”
Section: Resultssupporting
confidence: 93%
“…The heritability estimate of the weaning weight of this study was greater than that of Fathoni et al [13] in OG cattle, namely 0.36 ± 0.21, the results of Suhada et al [16] in Simental cattle, namely 0.39 ± 0.16, the results of Putra's research in Aceh cattle, namely 0.48 ± 0.58, and from the result of Estrada-León et al [17], namely 0.43 ± 0.09, but lower than the results of Karnaen [15] research in Madura cattle, namely 0.87 ± 0.45. The heritability estimate of the weaning weight of this study was not different form that of Lopez et al [19] result on Hanwoo cattle, which was 0.51 ± 0.03.…”
Section: Resultscontrasting
confidence: 79%
“…The average and standard deviation is 24.1 and 2.3 months ( Table 2 ), respectively, which is lower than 24.7 and 25.1 age month obtained by Eum et al [ 8 ] and Lopez et al. [ 9 ]. The AFC in Hanwoo heifers seems to be lower than that of most beef cattle breeds [ 10 – 12 ], which ranges from 28 to 34 months old with seasonal breeding.…”
Section: Resultscontrasting
confidence: 57%
“…3 shows the distribution of CIs, ranging from 300 to 620 days, with the mean and standard deviation of 399.0 and 101.1 days ( Table 2 ). Cho et al [ 27 ] have reported similar values for the mean of CIs, while Eum et al [ 8 ] and Lopez et al [ 9 ] have reported much lower values of 360.8 and 363.1 days in Hanwoo.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation